2010
DOI: 10.2215/cjn.09001209
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal proBNP—Marker of Cardiac Dysfunction, Fluid Overload, or Malnutrition in Hemodialysis Patients?

Abstract: Background and objectives: N-terminal probrain type natriuretic peptide (NTproBNP) has been proven to be a valuable biomarker for predicting cardiac events and mortality in the hemodialysis population. However recent reports have suggested that NTproBNP is a marker of volume overload rather than one of cardiac dysfunction. Therefore this study investigated the effect of fluid volume status on NTproBNP.Design, setting, participants, & measurements: Volume status was determined pre-and postdialysis in 72 stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
136
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(150 citation statements)
references
References 19 publications
11
136
0
3
Order By: Relevance
“…28 In another study by Booth et al, a strong association was found between NT-proBNP and the predialysis ratio of extracellular water/total body water. 29 Our study agrees with these previous reports by showing that NT-proBNP was significantly higher in the CKD patients with overhydration compared to patients without, and it was significantly positively correlated with OH/ECW (reflecting overhydration).…”
Section: Discussionsupporting
confidence: 93%
“…28 In another study by Booth et al, a strong association was found between NT-proBNP and the predialysis ratio of extracellular water/total body water. 29 Our study agrees with these previous reports by showing that NT-proBNP was significantly higher in the CKD patients with overhydration compared to patients without, and it was significantly positively correlated with OH/ECW (reflecting overhydration).…”
Section: Discussionsupporting
confidence: 93%
“…Multi-frequency bio-impedance is being increasingly used to assess volume status in peritoneal [17] and haemodialysis patients [18]. As the water content of different tissues varies, for example being greater in muscle compared to fat, bioimpedance can be used to assess body composition, with comparable results to dual energy X ray absorptiometry [19].…”
Section: Discussionmentioning
confidence: 99%
“…Notable is that TnT has molecular size of 37 kDa but also exists as fragments ranging in size from 8 kDa to 30 kDa (26,27), and troponin I has size between 21 kDa to 24 kDa (28). The cardiac markers are all predictors of increased risk of mortality (13,17,18,21,24,(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%